Narrativas: elementos constitutivos da formação de professores no âmbito dos cursos pré-vestibular - quem somos e para onde vamos - Nascimento, Edson Ricardo Nunes (Universidade Federal de São Carlos, 2022)
Popular preparatory courses have always been part of my history. I began my journey with them in my third year of high school, when I was a student at the FEAUSP preparatory course. Throughout my undergraduate studies, I have always been involved in projects related to teaching, and in 2018 I enrolled in the popular preparatory course for university entrance exams at UFSCar in Araras, UFSCurso, where I had my first experiences with teaching and extension projects. Throughout the history of popular preparatory courses, their role in society has always been based on the idea of ​​bringing a liberating education to the most needy segments of society. Despite their formative nature, within a non-formal education, popular preparatory courses can be highly formative environments, both for educators and students. From there, this work aims to understand the formative potential within the scope of popular preparatory courses, and mainly what are the formative needs constructed throughout teaching within UFSCurso, and the role of formative extension (communication). As a result, the research showed that the UFSCar Popular Preparatory Course in Araras, as a great teacher trainer, proved to be very effective in theory and practice, especially in creating the teaching identity of its extension workers. In addition, the practice of extension as communication was present in the relationship between students and teachers, although there are crucial points for it to successfully perform its role as a trainer of cognitive and critical subjects. Words-
Narratives: constituent elements of teacher training in pre-university courses - who we are and where we're going
Keywords: Cursinhos populares; Formação de professores; UFSCurso; Pré-vestibular; Ensino; Teacher training; Teaching; Pre-university; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO::ESTRUTURA E TRANSFORMACAO DO ESTADO